Falls and Related Injuries in Hospitalized Patients With Cancer in Taiwan. Issue 4 (August 2017) - Tsai, Li-Yun; Campbell, Malcolm; Chen, Ching-Ju; Hsieh, Ruey-Kuen; Chien, Hui-Hsien; Tsai, Jung-Mei
ABSTRACT: Background: Falls and fall-related injuries are important indicators for quality of nursing care in institutions. Few studies have been conducted specifically on this topic for hospitalized patients with cancer in Taiwan. Purpose: The aims of this study were to understand falls and levels of injury; to identify associations among fall-related injuries, demographics, and causes of falling; and to predict fall-related injuries in hospitalized patients with cancer. Methods: A retrospective survey design was used. Data were retrieved from the Taiwan Patient-Safety Reporting system query fall incidences for persons hospitalized with cancer at a medical center in northern Taiwan from 2010 to 2012. Data were encoded and analyzed with descriptive statistics, the chi-square test, and multiple stepwise logistic regression analysis using IBM SPSS Statistics version 18.0. Results: One hundred fifty-six (85%) of the 184 hospitalized patients with cancer had fall-related injuries. Falling tended to be more frequent in men without a history of falls and more prevalentat night. The results of regression analysis showed that the variables being with companions at the time of a fall ( OR = 5.411, 95% CI [1.619, 18.081]), lower limb weakness ( OR = 0.284, 95% CI [0.097, 0.832]), postural hypotension ( OR = 0.101, 95% CI [0.014, 0.733]), total score of fall risk factors ( OR = 1.688, 95% CI [1.071, 2.660]), and a fall occurring at the bedside ( OR = 3.493, 95% CI [1.119, 10.903]) were all positively associated with fall-related injuries, with a Nagelkerke R 2 of 42.8%. Conclusions/Implications for Practice: The risk factors for falls that affect hospitalized patients with cancer are complex. Nursing staff must evaluate the risk factors and treatment methods for each patient and facilitate fall prevention measures to achieve safety-centered quality of care. This study provides an example for nursing staff when assessing factors associated with falls and working to reduce fall-related injuries among patients with cancer.